Forming of skills to solve the creative tasks for the students of engineering profile - Dubovez, A.; Ruban, N. (Problems of Engineer-Pedagogical Education, 2018)
The work describes the technique of forming the skills for the engineering students to solve the creative tasks related to the upgrading the existing facilities based on the known principle, according to which the facility being improved works, without getting into experimental researches. The proposed technique is implemented based on the algorithm. The efficiency of the technique is shown on certain examples, namely on the measurement means – floating level gages. As a basic law, we have selected the law, on which basis the primary converter – sensitive element of the measurement mean - operates, and its output signal is converted further to the particular measurement result. In order to improve the facility it is suggested to convert the basic law into the form, when the law formula has the values, which are not measured, excluded, and the same will provide the conditions for avoiding the additional errors in the results of automatic control and adjustment. Under these conditions the students are suggested to develop the facility diagram, to describe it, to make conclusions and to determine the advantages and its field of application. The proposed technique will enable to form the creative thinking of the students as well as the skills to solve the creative tasks, without need in complicated experimental units, will enable to perform the search of the target product, as presented in formalized format, individually and collectively.